2018
DOI: 10.1109/tcad.2017.2775227
|View full text |Cite
|
Sign up to set email alerts
|

Image Edge Detection Based on Swarm Intelligence Using Memristive Networks

Abstract: Abstract-Recent advancements in the development of memristive devices has opened new opportunities for hardware implementation of non-Boolean computing. To this end, the suitability of memristive devices for swarm intelligence algorithms has enabled researchers to solve a maze in hardware. In this paper, we utilize swarm intelligence of memristive networks to perform image edge detection. First, we propose a hardware-friendly algorithm for image edge detection based on ant colony optimization. Second, we imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, it was shown that implementing a swarm intelligence algorithm of image edge detection with circuits of memristors consumes less energy than conventional methods. 18 Exploring other swarm intelligence ideas and different substrates to implement them is an exciting road towards low energy cost systems that perform complex optimization tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown that implementing a swarm intelligence algorithm of image edge detection with circuits of memristors consumes less energy than conventional methods. 18 Exploring other swarm intelligence ideas and different substrates to implement them is an exciting road towards low energy cost systems that perform complex optimization tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Pershin and Di Ventra proposed to solve the shortest path problem directly in hardware, using nanodevices called memristors, which have dynamics that provide reinforcement mechanisms similar to the ones at play in the ant colony optimization. [15][16][17][18] Memristors are defined by having conductances that change when subjected to electrical current. [19][20][21] As a voltage is applied to a network of memristors forming a graph, more current will flow through the shortest branch because that branch has the lowest resistance.…”
Section: Introductionmentioning
confidence: 99%
“…More bespoke implementations depart further from the conventional crossbar or neural network architectures and replace the dot product entirely. Fuzzy XOR gates implemented with memristors can determine pixel gradients (Merrikh-Bayat et al, 2014) and swarm computations, based on the behavior of ants, have been replicated with grids of memristors (Pajouhi and Roy, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A key element of any such algorithm is the detection of edge points in noisy images, which is an ongoing field of research. [4][5][6][7] We base our work on the idea of rotational difference kernel estimators (RDKE) from Qiu, 8,9 further improved by Garlipp and Müller. 10 Chu et al 11 combine these results with a kernel smoothing method to estimate jump location curves.…”
Section: Introductionmentioning
confidence: 99%